2021
DOI: 10.1186/s41936-020-00199-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Petiveria Alliacea (Linneaus) leaf and root bark powder in the control of filariasis vector Culex Quinquefasciatus

Abstract: Background Mosquitoes are vectors of parasitic diseases such as malaria, lymphatic filariasis, yellow fever, and dengue fever among others. They are well known as public enemies for their noise nuisance, biting annoyance, sleeplessness, allergic reactions, and diseases transmission during the biting and feeding activities. This then necessitate the search for insecticides of plant origin which are bio-degradable, non-toxic, and readily available for man use. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These results showed that the P. alliacea leaf extract contained antinociceptive compounds [52]. alliacea might be a dependable source of insecticide to produce biopesticides [40].…”
Section: Immuno-stimulating Propertiesmentioning
confidence: 81%
See 2 more Smart Citations
“…These results showed that the P. alliacea leaf extract contained antinociceptive compounds [52]. alliacea might be a dependable source of insecticide to produce biopesticides [40].…”
Section: Immuno-stimulating Propertiesmentioning
confidence: 81%
“…For several years, researchers have assumed that a single compound is responsible for a plant's biological activity, but recently, considering the possibility of synergy between compounds in a plant has been embraced [38]. Studies have revealed that crude extracts of P. alliacea exhibit antisickling [39], fumigant toxicity [40], insecticidal [41], anticancer, antidiabetic, anti-inflammatory, immune stimulant, and antibacterial activities [2]. for the bioactive potential.…”
Section: Nutritional Food Uses and Applications Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a flowering plant that is indigenous to the Caribbean, Central America, the United States, Mexico, and tropical South America [15]. The plants are herbaceous shrubs with small green flowers and a deep root system that can reach heights of 1 m. The leaves and roots have a strong aroma resembling that of garlic [16]. It is a wellknown medicinal herb in many tropical regions.…”
Section: Introductionmentioning
confidence: 99%